The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/oemed-2015-102900
|View full text |Cite
|
Sign up to set email alerts
|

Does cadmium exposure contribute to depressive symptoms in the elderly population?

Abstract: Owing to inconsistent results in analyses between blood cadmium levels and depressive symptoms, we cannot conclude any solid association between blood cadmium levels and depressive symptoms in the elderly population. To clarify the relationship, other prospective studies are needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In support of this decision, mean blood cotinine level in non-smokers is 10.93 ng/ml in our study, suggesting that it is present in nonsmokers and is important to include in the model. Another recent study of 395 elderly (age > 60) people living in Seoul, South Korea, also found a positive association between BCd and depressive symptoms, and while they did attempt to stratify by smoking status, they had very few current (23 people) and former (24) smokers in their sample (Han et al, 2016). Taken as a whole, these studies generally controlled for urine or serum cotinine, a sensitive and specific biomarker of current tobacco exposure (Bramer and Kallungal, 2003) but they did not control for pack-years, an indicator of long-term smoking exposure.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In support of this decision, mean blood cotinine level in non-smokers is 10.93 ng/ml in our study, suggesting that it is present in nonsmokers and is important to include in the model. Another recent study of 395 elderly (age > 60) people living in Seoul, South Korea, also found a positive association between BCd and depressive symptoms, and while they did attempt to stratify by smoking status, they had very few current (23 people) and former (24) smokers in their sample (Han et al, 2016). Taken as a whole, these studies generally controlled for urine or serum cotinine, a sensitive and specific biomarker of current tobacco exposure (Bramer and Kallungal, 2003) but they did not control for pack-years, an indicator of long-term smoking exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Although recent studies that have shown a link between BCd and depressive symptoms did adjust for smoking (Berk et al, 2014; Han et al, 2016; Scinicariello and Buser, 2015), their models may still have been susceptible to residual confounding. The Berk et al (2014) study using NHANES 2005–2010- the same population as our study - found an association between BCd and depressive symptoms, defined like our study as PHQ-9 score ≥ 10, for the upper quartile of BCd (OR 1.48 95% CI 1.16–1.90).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thank Dr Tomoyuki Kawada1 for his interest in our manuscript entitled ‘Does cadmium exposure contribute to depressive symptoms in the elderly population?’2 In the letter, Dr Kawada depicted three possible reasons for the inconsistent results of our study: limited statistical power, use of blood cadmium as marker of cadmium exposure and the presence of other potential confounding variables.…”
mentioning
confidence: 98%
“…Han et al 1 investigated the association between blood cadmium levels (B-Cd) and depression in 395 people, aged 60 years or older. Survey was conducted three times, and positive association between B-Cd and depression was only observed in the first visit.…”
mentioning
confidence: 99%